Emotional Status of MalaysianTeachers on Online Teaching during the COVID-19 Pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines Malaysian teachers’ (N=47) emotions on online teaching during the COVID-19pandemic. Data for this study were collected using an online questionnaire, and the results showed that teachers only agreed that they have positive emotions (M=3.64, SD=0.34) on the fully online teaching caused by the COVID-19 pandemic around the world. Teachers present different emotions due to their gender, grade taught, years of teaching experience, and subject taught.